Las TIC/TAC: subjetividades de los jóvenes universitarios en Montería (2020)
This paper analyzes the subjectivities that are being generated in the university students in Monteria on these technologies and the educational transits that occur with it. Therefore, a case study was carried out, from known subject epistemology perspective. Information collection was done by means of participant observation, focus groups, life relates-histories and digital narrations. Participants were 28 young students between 18 and 23 years from different undergraduate programs. Among conclusions, ICT/ACT have a preponderant role in the construction of subjectivities of young people; therefore, they could foster the development of a critical subject with access to a large amount of information that, in certain circumstances, would turn knowledge into knowledge; nevertheless, they also could generate a passive subject to information, consumer and with few intellectual processes. In this sense, some subjects are being replicated, copied, transferred, indeed, Young Cyber-homogenized, which are connected by cyberspace, but which are simultaneously homogenized through their dress, body building, and ways of relating.